Influenza virosomes as vaccine adjuvant and carrier system. (July 2013) - Moser, Christian; Müller, Matthias; Kaeser, Matthias D; Weydemann, Ulrike; Amacker, Mario
The basic concept of virosomes is the controlled in vitro assembly of virus-like particles from purified components. The first generation of influenza virosomes developed two decades ago is successfully applied in licensed vaccines, providing a solid clinical safety and efficacy track record for the technology. In the meantime, a second generation of influenza virosomes has evolved as a carrier and adjuvant system, which is currently applied in preclinical and clinical stage vaccine candidates targeting various prophylactic and therapeutic indications. The inclusion of additional components to optimize particle assembly, to stabilize the formulations, or to enhance the immunostimulatory properties have further improved and broadened the applicability of the platform.